Exploring children's socialization to three dimensions of sustainability. Issue 2 (10th June 2014) - Elizabeth Francis, Julie; Davis, Teresa
Abstract : Purpose: – This study aims to examine aspects of children's sustainability socialization. Many studies examine children's attitudes to sustainability. However, few studies build an understanding of how, where and when children are socialized to sustainability. Design/methodology/approach: – Interviews with 30 children explore the socializing agents (who), learning situations (where), learning processes (how) and learning effects (what). The study also delineates and compares the environmental, self and social dimensions of sustainability. Findings: – Socialization to environmental sustainability is highly structured and formal, and children rarely go beyond the knowledge and actions they are taught. Socialization to the self dimension combines formal and informal mechanisms with a greater propensity for elaboration and generalization. Meanwhile, socialization to societal sustainability involves unstructured and individualized processes and outcomes. Research limitations/implications: – This is an exploratory study. Future research could develop scales to measure children's sustainability dispositions and actions. Researchers could then use such scales to examine the sustainability socialization of children from other demographic and cultural groups. Practical implications: – The findings indicate that children are often positively disposed towards sustainability but lack the knowledge and direction needed to exercise this desire. Thus, marketers should more clearly articulate how their product solves a sustainability problem. Social implications: – This paper could inform sustainability education policy. It has practical applications in the area of sustainability curriculum design in schools. Originality/value: – Being the first study that explores children's socialization to three dimensions of sustainability, this paper provides a unique contribution to consumer behaviour theory and would be of interest to academics, practitioners and social marketers.